Government-Controlled Firms: Recent Discussion and Future Research Direction - wisnu untoro (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
Studies on the existence and roles of government-controlled firms have moved forward along with the globalization and the advancement of technology. After many discussions on the performance difference between state and private firms and subsequently the impact of privatization, recent discussion is dominated by the implementation of corporate governance and modern business strategy. In this paper, I provide the recent literature and discussion on the existence, role and performance of government-controlled firms. Moreover, some future research directions are discussed